The Relationship between Incentives and Years of Service with Nurses' Performance in Documenting Nursing Care - Mayenti, Fitra; Mustika, Aai; Mulyadi, Romi (Universitas Fort De Kock Bukittinggi, 2025)
Background: Nurses are one of the professions in hospitals that have an important role in the provision of health services. Therefore, hospitals where nurses work are always making various efforts aimed at improving the quality of nurse professionalism. Nurse performance is a problem that must be addressed immediately, because nursing services determine the quality of hospital services.Purpose: This study aims to determine the relationship between incentives and length of service with nurse performance in documenting nursing care at Indrasari Regional General Hospital.Methods This type of research is quantitative with a cross-sectional approach. The number of samples in this study was 79 people. The sampling technique used was Probability Sampling with Proportionate Stratified Random Sampling. The statistical test used was the Pearson chi-square test.Results : The results showed that the majority of nurses' incentives (71 respondents (89.9%) were categorized as available, the majority of nurses' length of service (64 respondents (81.0%) were ≥5 years, and the majority of nurses' performance was categorized as moderate (53 respondents (67.1%). The results of statistical tests show that there is a significant relationship between incentives and length of service with nurse performance in documenting nursing care (P value 0.02 and P value 0.03).Conclution: It is hoped that the hospital will prioritize the needs of nurses in improving competence, providing incentives according to workload, and adding facilities in order to improve the quality of health services to patients.